Nanti Dampak Pendidikan Agama Kristen Terhadap Perubahan Karakter dan Perkembangan Keterampilan Profesional di Era Digital - Chanita Christie; Juanda Yulianus; Kezia Verena; Lia Lesty S; Lidiawati Lidiawati (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
With the rapid development of technology in the digital era, there have been changes in character and the development of professional skills in society. Where this affects the ethics and behavior of today's young generation, for this reason this study was conducted on an urgent need to analyze the impact of Christian Religious Education in balancing technological mastery with a strong moral foundation. The purpose of this study is to understand how Christian religious education can shape students' character, such as honesty, responsibility, and ethics, as well as develop the professional skills needed in the digital workplace. This study uses a qualitative methodology with a case study approach, where data is collected through in-depth interviews, observations, and document analysis from several Christian educational institutions. How Christian religious values ​​are integrated into the learning process to form a better personality, and how students can develop digital skills and soft skills such as leadership and communication, are the main topics of discussion in this study. Christian religious education plays an important role in producing students who are not only technically competent but also have strong moral integrity is the core of the study. This study has been shown to have a positive impact on the transformation of students' personalities and supports the development of professional skills that are relevant to the digital era.